Application of cylindrical phase shift migration algorithm with vector coherence factor(CPSM-VCF) on Ultrasonic Imaging Detection of Bearing ring - Dai, Shu-Tong; Wang, Xiao-Kai; Guan, Shan-Yue; Li, Yi-Xuan; Li, Li (2023 IEEE Far East NDT New Technology & Application Forum (FENDT), 2023)
Precision bearings are key transmission components of high-speed machine tools, trains and industrial robots, which always under high load and high-speed work condition. Internal cracks can easily cause the fracture failure of the bearings. Therefore, this paper proposes a cylindrical phase shift migration (CPSM) algorithm combined with vector coherence factor(VCF) for ultrasonic imaging detection of bearing rings. First, raw ultrasonic data is acquired by scanning along a circumference direction of a cylinder. The phase of the ultrasonic data is calculated through the Hilbert transform and Euler formula. The sine and cosine value matrixes of the phase are performed to construct the VCF. Then, the CPSM image reconstructed from original ultrasonic field is weighted by VCF. Finally, the image reconstructed by CPSM-VCF method is obtained. To verify the effectiveness of the above method, water immersion ultrasonic testing experiment of cylindrical specimen and rolled bearing ring was carried out. The results show that the signal-noise ratio (SNR) and lateral angular resolution of the reconstructed image were improved by CPSM-VCF. This research provides an efficient and low-cost ultrasonic imaging algorithm to detect rolled bearing rings.